Synthesis of Some Novel Substituted (per-O-acetyl-b-D-Glucopyranosyl)thioureas from 2-Amino-4-(4-methoxyphenyl)-6-phenylpyrimidines - Dinh Thanh, Nguyen (Asian Journal of Chemistry, 2011)
Some tetra-O-acetyl-b-D-glucopyranosyl thioureas was synthesized from peracetylated b-Dglucopyranosyl isothiocyanate and corresponding 2-amino-4,6-diarylpyrimidines using conventional and microwave-assisted procedures. The second procedure afforded higher yields in much shorter reaction times.